Spatial and temporal features of life expectancy of the population in the countries of Southwest Asia - I. Hossin (Наука. Инновации. Технологии)
Introduction. The study is devoted to a comparative analysis of the spatio-temporal features of life expectancy in Muslim countries of Southwest Asia in 1990–2020.Materials and research methods. Statistical data from the United Nations, the World Bank, the UNESCO Institute of Statistics and the World Health Organization were used as sources. Various research methods were used, including comparative geographical, graph-cartographic, and correlation analysis. The dependence of life expectancy on economic resources was revealed using the Preston curve.Research results and their discussion. The general and country trends of changes in life expectancy in the region are investigated. The peculiarities in the change in the difference between the life expectancy of men and women have been established. A typology of countries by life expectancy and the nature of its change is proposed. The main factors affecting life expectancy are identified, in the frequency of mortality, per capita spending on education and health care, the value of GDP (PPP $) per capit.Conclusions. Life expectancy in most Muslim countries of Southwest Asia is higher than the global average, significantly differing between them. There are three groups of countries – with high, above average, average and low life expectancy. Each group is characterized by different rates of change of the indicator. The average life expectancy of women is higher than that of men within the same limits as in most countries of the world. However, the instability of the geopolitical situation in the region leads in some cases to a significant increase in the gap due to the increase in male mortality. The value of life expectancy depends on a set of factors, but the most significant among them are mortality, per capita income, and the development of healthcare.